Percepcija ekološke ogroženosti in osebne (ne)moči ter ekološka aktivnost - Fabjančič, Nina (Teorija in praksa, 1997)
On the basis of survey data the author analyses factors which influence ecological engagement, i. e. participation in collective actions aimed at solving environmental problems. Two factors are examined: (1) sense of being endangered by different sources of pollution and (2) sense of power or belief that a person is able to contribute to the solving ecological problems. These two factors are derived from two theories of social movements: deprivation theory and resource mobilisation theory. The results of data analysis indicatethat both factors examined, have a significant influence on ecological engagement which means that the combination of both theories offers a better explanation of ecological engagement than each theory by itself although they originally oppose each other.
Keywords: ecology; ekologija; ekološka zavest; ekološka kriza; angažiranost; zaznavanje; družbena gibanja; raziskave javnega mnenja